Treatment of urban wastewater discharged into Tinh Tam lake using hydrogen peroxide-supplemented aerated biofilter system - Dang, Thi Thanh Loc; Van Tuan, Le (Hue University Journal of Science: Natural Science, 2025)
This study investigates the application of a hydrogen peroxide-supplemented aerated biofilter system (ABF-H₂O₂) for the treatment of urban domestic wastewater from the Tinh Tam Lake catchment area, located within the Imperial Citadel of Hue City, Vietnam. In the absence of centralised treatment facilities, untreated sewage from a combined sewer system is directly discharged into this ecologically and historically significant lake. A laboratory-scale ABF-H₂O₂ reactor was designed and operated over 45 days, treating both synthetic and actual urban wastewater. Key operational parameters included organic loading rate, hydraulic retention time, and H₂O₂ dosage. The system achieved removal efficiencies of 69–81% for chemical oxygen demand and 88–94% for five-day biochemical oxygen demand. Ammonium (NH₄⁺–N) removal reached 87% under low-loading conditions but declined to 27% at higher organic loading rates. H₂O₂ supplementation improved dissolved oxygen availability, supporting microbial activity and treatment stability under elevated stress. Microscopic analysis revealed a diverse and well-adapted microbial community, including protozoa and metazoa. These results highlight the potential of the ABF-H₂O₂ approach as a sustainable and decentralised wastewater treatment solution for urban heritage areas such as the Imperial City of Hue City.